Pengembangan Kreativitas Anak Melalui Kegiatan Interaktif yang Hemat, Menarik dan Menyenangkan dengan Patuh Protokol Kesehatan Di Era Ekonomi New Normal - Mugiono; Dian Ari Nugroho; Atikah Nur Aini Putri; Nahdiah Hilmi Nur Fatin (Future Science, 2023)
This community service activity is motivated by efforts to empower the community-based creative economy in the new era after the current Covid-19 pandemic. The objects of this community service activity are children in tourist villages in Malang City, namely: Colorful Villages and Blue Villages on the banks of the Brantas river in Malang City. The purpose of implementing this activity is to increase the creativity of school-age children, ban them from the habit of saving life through fun interactive games, and instill positive attitudes from an early age. Activities carried out for children in tourist villages include interactive game activities, quizzes, teaching and tutoring for children. The implementation was carried out for two full days in two different weeks, at the Al-Kahfi Embong Brantas Malang Foundation. The children assisted by the Foundation and the Al-Kahfi Foundation were very enthusiastic about attending and participating in this series of community service activities. The results of this community service activity can be in the form of direct or indirect results for the development of a community-based creative tourism economy. The results were immediately felt by the children who were the targets of this activity. Children become aware of creative activities that can be done in the environment. They will become accustomed to creatively utilizing the resources in their environment, and they will become accustomed to being more economical in carrying out their daily play activities in the new normal era. It is hoped that this positive learning will leave an impression on their subconscious. Indirect results can be obtained from the tourism village community, with children who are more active and creative who can add added value and attractiveness to the tourist village itself.